Digitalisasi Literasi Matematika Pada penguatan Konsep Komputasi Geometri Berbasis Geogebra - Sigit, Miftah; Dewi Astria Faroek; Faida Musa’ad (Ilin Institute, 2025)
This community service research focuses on the implementation of digital mathematics literacy to strengthen the concept of geometric computation based on GeoGebra in Sorong City. This research enhance educators' capabilities in using GeoGebra technology in classrooms. The community service aims to extend of mathematics education with the theme of digital literacy, provide training in the use of GeoGebra, and distribute the GeoGebra Teaching Guide Compilation books to schools. The results show an increase in teachers' abilities and enthusiasm in using GeoGebra as a teaching aid for mathematics, as well as the achievement of long-term educational.